Pattern of Ocular and Ear Morbidity Among Electric Rickshaw Drivers of Biratnagar Metropolitan City, Nepal: - Adhikari, Pankaj Ray; Aara, Tabassum; Karn, Rajiv Ranjan (Birat Journal of Health Sciences, 2025)
Introduction: Vision is a fundamental component of safe driving. Any significant loss of visual function such as vision, field of vision, color vision, or contrast sensitivity/ability to see light and traffic signals in bad weather and night will diminish a person’s ability to operate a motor vehicle safely on today’s congested high-speed roadways. Objectives: To find out the pattern of ocular and ear morbidity of city rickshaw driver of Biratnagar metropolitan city. Methodology: The descriptive cross-sectional study was conducted at Biratnagar Eye Hospital (BEH), Biratnagar. The socio-demographic variables, assessment of uncorrected and corrected visual acuity for distance and near, color vision, stereopsis/depth perception, anterior and posterior segment ocular examination was done. Ear examination was performed by using otoscope and torch light. Results: Among 154 participants, mean age (±SD) was 38.09(±9.66) and all of them were male 154(100%). Nearly half 74(48%) of the participants were in the age group 26-40 years among them majority had completed secondary level education 94(61%) and 121(78.6%) had no driving license. More than half of the participants 79 (51.3%) reported previous history of eye examination. Normal color vision and stereopsis was found in 142(92.2%) and 89(57.8%) participants respectively. Majority of them 306(99.35%) had normal best corrected visual acuity. Only 2 of them had history of Road Traffic Accident (RTA). More than two-thirds of the participants had no ear morbidity. Conclusion: Distance visual acuity was found good but presbyopia was the most common ocular morbidity and stereopsis was found abnormal among electric rickshaw driver. Majority of them had no ear morbidity